THU0548 Standardised procedures for ultrasound imaging in paediatric rheumatology: progress of eular/pres task force. (12th June 2018) - Vojinovic, J.; Collado, P.; Janta, I.; Carmona, L.; Malattia, C.; Magni-Manzoni, S.; Susic, G.; Tzaribachev, N.; Ravagnani, V.; Rossi-Semerano, L.; Kljucevsek, D.; Lanni, S.; et al.
Abstract : Background: Musculoskeletal ultrasound (MSUS) is dependent on sensitivity of the machine used and the skills of the operator. Additional specificities are unique features of the growing skeleton, which include age-related variation of the thickness of the articular cartilage (due to incomplete ossification) and the presence of physiologically detected vascularisation even in healthy children. Objectives: EULAR/PReS task force objective was to develop EULAR/PReS Standardised Procedures for Ultrasound Imaging in Paediatric Rheumatology through a consensus process among rheumatologists, paediatric rheumatologists, and radiologists highly experienced in the performance, teaching and research in paediatric MSUS in rheumatic diseases. Methods: In the first phase we performed a systematic literature review (SLR) on guidelines for MSUS for children endorsed by international societies and articles on how to perform MSUS scanning in children. Based on the SLR results, project conveners formulated a Delphi survey by selecting the items to be included (i.e. musculoskeletal anatomic structures evaluable by US, scanning technique, and their lesions/abnormalities detectable by US at the principal joint areas). The Delphi survey was distributed among a broad panel of experts in MSUS, selected for their high experience in the performance, teaching and research in MSUS in children. Based on the Delphi results the main anatomical structures (for definitions, photo and video recordings) were selected to be analysed in the final phase organised as an exercise on live healthy children models. The meeting involved: 16 project participants (13 paediatric US experts, fellow, as well as, AHP and PARE representatives), 16 healthy children models (representing four different age groups) accompanied by their parents (who had signed informed consent to participate), 4 photo/imaging technicians, 2 expert technicians in US machines. Results: Structures from 8 musculoskeletal areas (i.e. shoulder, elbow, wrist and hand, hip, knee, ankle and foot) in 4 age groups of children were selected. Detailed scanning procedures (i.e. patient position, probe placement, scanning method and bony/other landmarks) were defined. We recorded the reference photo (live and US image) and video (procedure video clip and US video record) of the scanning procedures. As a result, we obtained photo and video image library with a detailed description of the standardised US procedures in children which can be used as EULAR/PReS web-based educational application. Conclusions: This task force has produced a consensus-based comprehensive and practical framework on standardised procedures for MSUS imaging in paediatric rheumatology. Disclosure of Interest: None declared